Optimization of supercritical CO2 extraction of phytosterol-enriched oil from Kalahari melon seeds. - Kar, Lin Nyam; Tan, Chin Ping; Lai, Oi Ming; Long, Kamariah; Che Man, Yaakob (Springer Verlag, 2011)
Supercritical carbon dioxide (SC-CO2) extraction of oil from Kalahari melon seeds was investigated in this study. Response surface methodology was applied to model and optimize the extraction, namely pressure (200–400 bar), temperature (40–80 °C), and supercritical fluid flow rate (10–20 mL/min). Well-fitting models were successfully established for oil recovery (R 2 = 0.9672) and phytosterol concentration (milligrams per 100 g; R 2 = 0.8150) through multiple linear regressions with backward elimination. The effect of supercritical fluid flow rate was the most significant (P < 0.05) factor that affected oil recovery but this factor had no significant (P > 0.05) effect on phytosterol concentration. The optimal processing conditions for oil recovery and phytosterol concentration were pressure of 300 bar, temperature at 40 °C, and supercritical fluid flow rate of 12 mL/min. These optimal conditions yielded a 76.3% oil recovery and 836.5 mg/100 g of phytosterol concentration. The oil content in the Kalahari melon seeds as estimated by Soxhlet extraction was around 30.5/100 g. The phytosterol concentration in the oil extracted with SC-CO2 extraction was 94% higher than that obtained with solvent extraction.